Young Investigator: David JR Conroy. (July 2011) - Conroy, David JR; Millner, Paul
Supervisor''s supporting comments As a graduate nanotechnologist, MSc bio-nanotechnologist David is one of the new breed of young scientists who only progress if they are prepared to develop a wide skill base and engage in a multiplicity of new techniques and approaches cutting right across the full range of scientific disciplines. David has shown himself to be a creative and lateral thinker who is totally committed to finding (and training in) the techniques he needs to accomplish his aim, which is translational research aimed at producing real world analytical devices that lean heavily on the new opportunities offered by bionanotechnology. The uranyl sensor he developed (now published work) really does show the way to remote environmental monitoring of pollutants. In fact, this makes possible an environmental surveillance approach that has hitherto been impossible except with huge expense and infrastructure. His work is likely to change current practice in a big way and he would be a very worthy recipient of a young investigator award.